Effects of Leader Contingent and Noncontingent Reward and Punishment Behaviors on Subordinate Performance and Satisfaction - Podsakoff, Philip M.; Todor, William M.; Skov, Richard B. (Academy of Management Journal, 1982)
This study investigated the nature of the relationships between leader reward and punishment behaviors and subordinate performance and satisfaction. Only performance?contingent reward behavior was found to affect subordinate performance significantly. Positive relationships were found between leader contingent reward behavior and employee satisfaction. Contingent punishment had no effects on subordinate performance or satisfaction.